The Influence of Product Innovation and Knowledge Management on Competitive Advantage: Study on Haus X Arief Muhammad Choco Cheese Crunchy Made With Kitkat - Citra, Adriana Widya; Hatammimi, Jurry (Dinasti Publisher, 2025)
Haus is a phenomenal contemporary beverage sector UMKM. Since its establishment in June 2018, it has expanded throughout Indonesia with 221 branches and more than 500 Huling (Haus Keliling) fleets. This study aims to analyze the impact of product innovation and knowledge management on Haus's competitive advantage. A quantitative approach with a causal design was employed to evaluate the influence of product innovation and knowledge management on competitive advantage. Using a purposive sample approach, 180 Haus customers in the Jabotabek region were given an online questionnaire to complete in order to gather data. The study's findings indicate that knowledge management and product innovation both partially and concurrently improve competitive advantage.